Geophysical, geotechnical, and vegetation characteristics in landslide areas in Pujon and Ngantang, Malang Regency, East Java - Zairina, Anisa; Soemarno, Soemarno; Rachmansyah, Arief; Yanuwiadi, Bagyo (Journal of Degraded and Mining Lands Management, 2024)
One of the efforts to manage the risk of ground movement is to identify landslide-prone area characteristics. This study aimed to investigate the geophysical, geotechnical, and vegetation characteristics of landslide and non-landslide areas. This study adopted the resistivity geoelectric method to identify the type and structure of subsurface materials in landslide and non-landslide regions in Pujon and Ngantang, Malang Regency. Measurements in this study were done in four locations. Each geoelectric measurement path at each location was determined to be 100 m long. The electrodes were spaced apart by 10 m for measurements between the current electrode and the potential electrode. The dipole-dipole configuration of the geoelectric survey trajectory is determined based on the former landslide event to predict underground material. In addition, an investigation of geological, geotechnical, and vegetation characteristics was carried out. The results showed that the geophysical, soil, and vegetation characteristics of the landslide and non-landslide slopes were similar. The geophysical characteristics of the soil in all study locations indicate the presence of a slipping surface, which makes the land prone to landslides. The slipping plane was formed due to differences in the types of rocks between the surface and deep layers. The existence of vegetation has an important role in landslide management. Non-landslide areas tended to have denser tree vegetation and a higher number of shrub species.